1997
DOI: 10.1128/jb.179.20.6271-6278.1997
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of an avilamycin biosynthetic gene cluster from Streptomyces viridochromogenes Tü57

Abstract: A 65-kb region of DNA from Streptomyces viridochromogenes Tü57, containing genes encoding proteins involved in the biosynthesis of avilamycins, was isolated. The DNA sequence of a 6.4-kb fragment from this region revealed four open reading frames (ORF1 to ORF4), three of which are fully contained within the sequenced fragment. The deduced amino acid sequence of AviM, encoded by ORF2, shows 37% identity to a 6-methylsalicylic acid synthase from Penicillium patulum. Cultures of S. lividans TK24 and S. coelicolor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(79 citation statements)
references
References 36 publications
1
77
0
1
Order By: Relevance
“…PctT is also highly homologous to ChlB3, ChlB6 [19], AviN [16], and CalO4 [17], all of which accompany with an iterative type I PKS. These homologous proteins were presumed to attach the starter unit, acetyl CoA, onto the corresponding PKSs, since FabH enzymes use an acyl-CoA rather than an acyl-ACP as the primer and catalyze the first condensation step in the pathway [55,56].…”
Section: Functional Analysis Of the Pctl Gene Encoding A Glycosyltranmentioning
confidence: 99%
See 1 more Smart Citation
“…PctT is also highly homologous to ChlB3, ChlB6 [19], AviN [16], and CalO4 [17], all of which accompany with an iterative type I PKS. These homologous proteins were presumed to attach the starter unit, acetyl CoA, onto the corresponding PKSs, since FabH enzymes use an acyl-CoA rather than an acyl-ACP as the primer and catalyze the first condensation step in the pathway [55,56].…”
Section: Functional Analysis Of the Pctl Gene Encoding A Glycosyltranmentioning
confidence: 99%
“…In actinomycetes, this type of simple aromatic polyketides is generally biosynthesized by an iterative type I polyketide synthase (PKS) [15], which has been quite recently established and are encoded in the avilamycin [16], calicheamicin [17], neocarzinostatin [18], chlorothricin [19], biosynthetic gene clusters. Therefore, an iterative type I PKS was also anticipated to be involved in the biosynthesis of pactamycin.…”
Section: Introductionmentioning
confidence: 99%
“…Rather recently, several bacterial PKS have been found that do not fit these model systems (21)(22)(23)(24)(25). For example, several iterative PKS have been discovered that contain one module located on a single protein analogous to fungal PKSs, and many of these PKS have been functionally characterized in heterologous hosts (26)(27)(28)(29). In addition, bacterial PKS were originally believed to be pantheinylated only by a discrete PPTase, but a PPTase integrated in a probable type I PKS has recently been described (30), thus resembling yeast FAS that contains a C-terminal PPTase on the ␣-subunit (31,32).…”
mentioning
confidence: 99%
“…10 The avilamycin resistance genes together with the structural genes were identified and cloned as an entire biosynthetic gene cluster containing 54 open reading frames. 11 The biosynthetic steps leading to the formation of the avilamycin molecule were established by the analysis of secondary metabolites produced by mutants. 11,12 Within the cluster also, two putative regulatory genes named aviC1 and aviC2 were identified.…”
mentioning
confidence: 99%
“…11 The biosynthetic steps leading to the formation of the avilamycin molecule were established by the analysis of secondary metabolites produced by mutants. 11,12 Within the cluster also, two putative regulatory genes named aviC1 and aviC2 were identified. Both genes are located in close proximity to each other and are transcribed in the same direction (Figure 1).…”
mentioning
confidence: 99%